Табор уходит в небо - Lotjanu, Emil (Soviet Union : Mosfilm, 1975)
This sensual melodrama based on early stories by Maxim Gorky tells the fatal love story between the beautiful and rebellious girl Rada and the handsome horse thief Zobar. The story is set in early 20th century Bessarabia, now part of Moldova, then to the Austro-Hungarian Empire.
Romology Film Collection
Keywords: Fiction films